2023
DOI: 10.3390/antiox12020461
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethanoid Glycoside-Enriched Extract Prepared from Clerodendrum chinense Leaf Inhibits A549 Lung Cancer Cell Migration and Apoptosis Induction through Enhancing ROS Production

Abstract: This study aims to investigate the antioxidant and anti-cancer activities of Clerodendrum chinense leaf ethanolic extract. The phenylethanoid glycoside-enriched extract, namely verbascoside and isoverbascoside, was determined in the ethanolic C. chinense leaf extract using the validated HPLC method. The ethanolic extract showed DPPH and ABTS free radical scavenging activities with the IC50 values of 334.2 ± 45.48 μg/mL and 1012.77 ± 61.86 µg/mL, respectively, and a FRAP value of 88.73 ± 4.59 to 2480.81 ± 0.00 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Several factors may have influenced the yield, including the temperature of extraction, extraction time, extraction solvent polarity, and the source of C. chinense stem [21]. The yield of C. chinense stem extraction was lower compared with C. chinense leaf (11.4%) and flower (11.2%) [18,19].…”
Section: Yield Of C Chinense Stem Extractmentioning
confidence: 99%
See 4 more Smart Citations
“…Several factors may have influenced the yield, including the temperature of extraction, extraction time, extraction solvent polarity, and the source of C. chinense stem [21]. The yield of C. chinense stem extraction was lower compared with C. chinense leaf (11.4%) and flower (11.2%) [18,19].…”
Section: Yield Of C Chinense Stem Extractmentioning
confidence: 99%
“…Among different parts of the plants, ethanolic extract of C. chinense leaf offered the highest TPC (1.03 g GAE/g extract), followed by stem extract (0.553 g GAE/g extract) and flower extract (0.487 g GAE/g extract) [18,19]. The results of total flavonoid content analysis showed that the stem of C. chinense exhibited the lowest concentration of total flavonoid content, followed by the leaf and flower [18,19]. These results indicated that each part of C. chinense contained different amounts of phenolic compounds and flavonoids.…”
Section: Total Phenolic Content and Total Flavonoid Content In C Chin...mentioning
confidence: 99%
See 3 more Smart Citations